Effects of sugarcane pressmud on agronomical characteristics of hybrid cultivar of eggplant (Solanum melongena L.) under field conditions - Vinod Kumar; A. K. Chopra (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The field experiments were conducted to utilize the sugarcane pressmud in the farming of Solanum melongena as an organic fertilizer. Methods For growing of S. melongena, six agricultural fields were selected for the six amendments of sugarcane pressmud, viz., 0 % (garden soil as control), 20 % (20 % sugarcane pressmud ? 80 % garden soil), 40 % (40 % sugarcane pressmud ? 60 % garden soil), 60 % (60 % sugarcane pressmud ? 40 % garden soil), 80 % (80 % sugarcane pressmud ? 20 % garden soil) and 100 % (100 % sugarcane pressmud). S. melongena was grown in sugarcane pressmud-amended soil till harvest and impact of sugarcane pressmud on the soil and agronomical characteristics of S. melongena were determined. Results The results showed that the sugarcane pressmud was rich in various nutrients and produced significant (P.05/P.01) changes in the soil characteristics in both seasons. Among various treatments, the maximum agronomic performance of S. melongena was observed due to 40 % treatment in both the growing seasons. The contamination factor (Cf) of various metals were recorded in order of Zn[Mn [Cd[Cu[Fe [Cr for the soil and Fe [Mn [Cu[Zn[Cd[Cr for S. melongena in both growing seasons after treatment with sugarcane pressmud. Conclusions This study concluded that application of sugarcane pressmud treatments increased the soil fertility and as a result agronomical performance of S. melongena. Therefore, it can be used for the soil amendments in the lower proportion (up to 40 %) to improve the yield of S. melongena.